Maximizar

Sujeto a:
3X1 + X2 = 3
4X1+3X2 ≥ 6
X1+2X2 ≤ 4
X1, X2 ≥ 0

Maximizar

Sujeto a:
3X1 + X2 + R1 = 3
4X1+3X2 + R2 – S1 = 6
X1+2X2 +S2 = 4

R1 = 3 – 3X1 – X2
R2 = 6 – 4X1 – 3X2 + S1
Reemplazando en funcion objetivo
Z – 4X1 – X2 + M(R1) + M(R2) = 0
Z – 4X1 – X2 + M(3 – 3X1 – X2) + M(6 – 4X1 – 3X2 + S1 ) = 0
Reduciendo:
Z – (4-7M)X1 – (1-4M)X2 + MS1 = 9M

3X1 + X2 + R1 = 3

B. Z X1 X2 S2 Z 1 0 0 0 Z 1 0 0 0 Z 1 0 0 0 X1 -4+7M 3 4 1 X1 0 1 0 0 X1 0 1 0 0 X2 -1+4M 1 3 2 X2 1/3+5/3M 1/3 5/3 5/3 X2 0 0 1 0 S1 -M 0 -1 0 S2 0 0 0 1 R1 0 1 0 0 S1 -M 0 -1 0 S2 0 0 0 1 R1 4/3-7/3M 1/3 -4/3 -1/3 S1 1/5 5/9 -5/3 25/9 S2 0 0 0 1 R1 16/15-M 3/5 -4/5 1 R2 0 0 1 0 R2 0 0 1 0 R2 -1/5-M -5/9 5/3 -25/9 Solución 9M 3 6 4 Solución 4+2M 1 2 3 Solución 18/5 3/5 6/5 1 . Z X1 R2 S2 V. Z R1 R2 S2 V.4X1+3X2 + R2 – S1 = 6 X1+2X2 +S2 = 4 V.B.B.

Sign up to vote on this title
UsefulNot useful